Strategi Komunikasi Mandorumah dalam Mewujudkan Eksistensi Slogan Kontraktor Anti Molor - Yanto, Heri; Mirza, Mochammad; Hardiyanti , Rini (Indo-MathEdu Intellectuals Journal, 2023)
The prevalent cases of stalled contractors have drawn attention within the construction industry. However, Mandorumah, a contracting company, has taken a different approach as the "Anti-Delay Contractor." Through qualitative research in the form of a case study, the focus lies on the company's communication strategies concerning quality, timeliness, and efficiency. Through direct observation and in-depth interviews, it was revealed that Mandorumah fortifies its image through social media, implements ongoing evaluations based on customer feedback, and engages actively in two-way communication with clients. As a result, Mandorumah has established a reputation as a reliable contractor. Their communication strategy, emphasizing customer satisfaction, effective utilization of social media, and continuous service evaluations, successfully portrays the "Anti-Delay Contractor" identity, highlighting reliability and trust in delivering projects to high standards and on time. Mandorumah serves as an exemplar in addressing challenges within the construction industry by committing to reliable and trustworthy outcomes